The Obstacle to Happiness: Early Maladaptive Schemas - S. Barbaros YALCIN; Mehmet AK; Mehmet KAVAKLI; Sahin KESICI (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The aim of this study is to determine whether individuals early maladaptive schemas predict their happiness levels or not and to find out what early maladaptive schemas prevent individuals happiness. Method: Relational screening model was used in the study. The study group consisted of the 253 university students; 198 (%78.3) females and 55 (%21.7) males. The Qxford Happiness Questionnaire Short Form, developed by Hills and Argyle (2002) and adapted into Turkish by Dogan and Cotok (2011), and Young Schema Scale-Short Form 3, developed by Young et al. (2003) and adapted into Turkish by Soygut, Karaosmanoglu, and Cakir (2009) were used to gather the data for the study. Results: According to the results obtained from the study, it was found out that there is a significantly negative relation between happiness and Vulnerability to Harm & Illness, Pessimism/Negativity, Failure, Social Isolation, Emotional Inhibition, Approval-Seeking and Insufficient Self-Control. Moreover, university students Pessimism/Negativity and Failure schemas were found to be the predictors of their happiness levels. Conclusion: Families, teachers and mental health workers should work together to resolve the Pessimism/Negativity and Failure early maladaptive schemas of university students. It is considered as a preventive measure that the education system must be reviewed. [JCBPR 2018; 7(1.000): 7-13]